Assessment of plant materials carbon sequestration rate for horizontal and vertical landscape design - Othman, Rashidi; Abu Kasim, Siti Zubaidah (IACSIT Press, 2016)
The excessive reliance of fossil fuels and carbon production from daily appliances especially in tourism accommodation premises could cause detrimental impact to the surrounding environment. This is due to the increase of carbon emissions which is one of the major contributors for greenhouse effect especially in urban area. In order to alleviate the carbon footprint by those premises, one of the promising method to reduce carbon dioxide emission to the atmosphere is by selecting an appropriate plant species as well as optimization of spatial organization of plant materials. Besides character of the plant materials, criteria such as locality, age, diameter and height are very much influenced the carbon sequestration rate. This study demonstrate that even with limited green space areas for tourism accommodation premises such as hotels and resorts, the carbon sequestration rate can be further increased with the right selection of plants, at the right place with the right landscape design. Therefore this study aimed to monitor, calculate and predict how much carbon can be absorbed by proposed plant species based on vertical and horizontal landscape design at certain period of time. The significance outcomes of this study will be green approach to monitor and sequester carbon toxicity using plant species also a novel landscape design approach to neutralize carbon emission which is cost effective and environmental friendly.